Retroviral integration sites correlate with expressed genes in hematopoietic stem cells - Wagner, Wolfgang; Maier-Laufs, Stephanie; Blake, Jonathon; Schwager, Christian; Wu, Xiaolin; Zeller, W. Jens; Ho, Anthony Dick; Frühauf, Stefan (Stem cells, 2005)
In this study, we analyzed whether retroviral integration sites in repopulating hematopoietic cells correlate with genes expressed in fractions enriched in hematopoietic stem cells (HSCs). We have previously described microarray studies of two populations enriched in HSCs: CD34+/CD38− and the slow dividing fraction of CD34+/CD38− cells (SDF). Furthermore, we demonstrated that oncoretroviral integrations in severe combined immunodeficient repopulating cells are preferentially located near the transcription start. Here, we have identified 117 corresponding cDNA clones on our micro-array representing genes with retroviral integration sites. These genes revealed a higher mean signal intensity in comparison with either all genes on the array or a subset of control genes with retroviral integrations in HeLa cells. Furthermore, these genes demonstrated a higher expression in CD34+/CD38− cells and SDF. The association of gene expression and retrovirally targeted genes observed here will help to elucidate the molecular characteristics of primitive repopulating hematopoietic cells.